Stereotactic radiation therapy for malignant choroidal tumors: preliminary, short-term results - Bellmann, Caren; Fuß, Martin; Holz, Frank G.; Debus, Jürgen; Rohrschneider, Klaus; Völcker, Hans Eberhard; Wannenmacher, Michael (Ophthalmology, 2000)
Purpose - To evaluate the role of stereotactic radiation therapy (SRT) in the treatment of malignant choroidal tumors. - Design - Prospective, noncomparative case series. - Participants - Ten patients with unifocal choroidal metastasis (three lung carcinoma, three breast carcinoma, three colon carcinoma, one cutaneous melanoma) and five patients with primary choroidal melanoma underwent single-dose or fractionated SRT. - Methods - Before treatment, computed tomography (CT) scans of the orbit were obtained with the patient wearing an individualized immobilization mask. An integrated macro-CCD-camera system viewed the eye for detection of movements. Three-dimensional computer-based treatment planning was carried out. Dose distribution was calculated and displayed in isodose lines on the CT data set. For SRT, a dedicated stereotactic linear accelerator (6 MV) was used. Total doses for choroidal metastases were 12 to 20 Gy in a single dose or 30 Gy over 10 days (3 Gy each session), and total doses for choroidal melanoma were 50 Gy over 5 or 10 days (10 or 5 Gy each session). - Main outcome measures - Best corrected visual acuity (ETDRS-chart), biomicroscopy, ultrasound examination, fluorescein angiography, and magnetic resonance imaging (MRI) were performed before treatment and at regular intervals after completion of SRT. - Results - During a follow-up period from 1 to 34 months (median, 6.5 months), local tumor control was achieved in all eyes. A decrease in tumor size on ultrasonography or MRI was noted in eight patients. No persistent side effects were observed during follow-up. - Conclusions - Stereotactic radiation therapy allows steep dose gradients outside the target volume by minimizing the field of exposure. Thus only low radiation doses affect surrounding radiosensitive ocular structures. Our initial findings suggest that this technique may be effective in controlling tumor growth. Further studies are needed to compare treatment efficacy and safety with conventional treatment methods.
Gesehen am 03.03.2021